'Confuse noises, and clatterings': fixed seating and disorderly worship in England, 1604-1632. Issue 5 (2nd September 2020) - Cioni, Francesca
ABSTRACT: Over the sixteenth and seventeenth centuries, fixed seating in box or bench pews was increasingly a feature of parish churches, with seating plans decided by churchwardens and leading parishioners, reflecting a complex network of social, economic and geographical relationships within the parish. Disputes over seating were frequent, largely litigated locally but occasionally rising to the Star Chamber or High Commission; these cases turn on charges of noise and disruption, a deep source of anxiety for the early modern Church. The Church's interest in maintaining order in worship lies behind the emphatic policing of "noise" in pew disputes as well as the practice of pewing itself. So frequent are such cases that the language of the pew dispute gains its own imaginative life, and its deployment in the period in religious and secular literature reveals the internal dissent and suspicion that can be seen to characterise the English Church.